The features of development of modern marine cruise tourism - Юрченко, Светлана; Юрченко, Елена; Кондрова, Александра (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
This article studies marine cruise tourism development at the modern stage; it shows that this sector of tourism market combines several tourism types and is profitable even within economic crisis conditions. The article dynamics of cruise tourism analyzes and reveals processes of deconcentration at the world tourism market. It reveales that European cruise market develops at a higher pace and it makes substantial contribution to European economics. The main tourism industry innovations on the modern cruise ships are characterized. The main traditional and new cruise routes are defined. The article shows that there is consolidation and merger of companies of the sea transportation market. The asticle gives characteristic of the three biggest cruise holdings.